Current vitamin D status in European and Middle East countries and strategies to prevent vitamin D deficiency: a position statement of the European Calcified Tissue Society - Lips, Paul; Cashman, Kevin D; Lamberg-Allardt, Christel; Bischoff-Ferrari, Heike Annette; Obermayer-Pietsch, Barbara; Bianchi, Maria Luisa; Stepan, Jan; El-Hajj Fuleihan, Ghada; Bouillon, Roger (European journal of endocrinology, 2019)
Vitamin D deficiency (serum 25-hydroxyvitamin D (25(OH)D) <50 nmol/L or 20 ng/mL) is common in Europe and the Middle East. It occurs in <20% of the population in Northern Europe, in 30–60% in Western, Southern and Eastern Europe and up to 80% in Middle East countries. Severe deficiency (serum 25(OH)D <30 nmol/L or 12 ng/mL) is found in >10% of Europeans. The European Calcified Tissue Society (ECTS) advises that the measurement of serum 25(OH)D be standardized, for example, by the Vitamin D Standardization Program. Risk groups include young children, adolescents, pregnant women, older people (especially the institutionalized) and non-Western immigrants. Consequences of vitamin D deficiency include mineralization defects and lower bone mineral density causing fractures. Extra-skeletal consequences may be muscle weakness, falls and acute respiratory infection, and are the subject of large ongoing clinical trials. The ECTS advises to improve vitamin D status by food fortification and the use of vitamin D supplements in risk groups. Fortification of foods by adding vitamin D to dairy products, bread and cereals can improve the vitamin D status of the whole population, but quality assurance monitoring is needed to prevent intoxication. Specific risk groups such as infants and children up to 3 years, pregnant women, older persons and non-Western immigrants should routinely receive vitamin D supplements. Future research should include genetic studies to better define individual vulnerability for vitamin D deficiency, and Mendelian randomization studies to address the effect of vitamin D deficiency on long-term non-skeletal outcomes such as cancer.